The challenges of industrial revolution (IR) 4.0 towards the teacher's self-efficacy - Najihah, Abd Wahid; Ismail, N.A.; Yusoff, A.S.M.; Wahab, N.A; Rahim, B.H.A.; Majid, N.A.; Din, N.M.N.; Ariffin, R.M.; Adnan, W.I.W.; Zakaria, A.R. (2020)
The emerging of IR . has brought a massive change in the world of education. In facing IR ., teachers today are urged to suit the process of teaching and learning. Hence, the teachers need to dominate the information technology because the new millennia students consist of z and alpha generation, who tend to utilize technology- based learning. Therefore, this study discusses how highly qualified teachers can cope with the current flow of revolution . according to current requirements. Findings show that high efficacy teachers in terms of student management, instructional strategies , and classroom management are willing to accept changes in teaching and learning. Besides, IR . has transformed the country's educational landscape from traditional- based learning to technology- based learning. IR . has enormous implications for the country's education system according to 21st-century learning needs.